Kemampuan Membaca Kritis Melalui Metode Deliberate Practice Pada Siswa Kelas V UPTD SD Negeri 48 Barru - Annisa; BESSE SYUKRONI; HASLINDA (STKIP Subang, 2025)
This study aims to improve the critical reading skills of fifth-grade students at the UPTD of SD Negeri 48 Barru through the application of the Deliberate Practice method. The study used Classroom Action Research (CAR) conducted in two cycles. The subjects were 18 fifth-grade students. The instruments used were a critical reading skills test, observation sheets, and documentation. The results showed a significant increase in students' critical reading skills after the implementation of the Deliberate Practice method. In the first cycle, the improvement did not reach the success indicator, but in the second cycle, students' critical reading skills reached the set target. Thus, the Deliberate Practice method is an effective learning strategy to improve elementary school students' critical reading skills.